The relationship between hygiene factors with job satisfaction among employees at the UiTM Kampus Kota Bharu / Nur Anisah Ghazali - Ghazali, Nur Anisah (Faculty of Business and Management, 2020)
The issues of job satisfaction are very paramount in the society these days especially among employees. This paper examines that motivates employee in the manufacturing industry, and examines their level of job satisfaction, using Herzberg’s hygiene factors. Therefore I decided to do a research about job satisfaction among employee to know and understand more about the factors that influence the job satisfaction and how to maintain a maximum job satisfaction among employees. The aim of these studies was to examine the direct and indirect relationship between job satisfaction and a few factors that I have identify such as interpersonal relationship, job security, salary and working condition. Job satisfaction of employee will encourage healthy and happy working environment of employees in an organization. Besides that, job satisfaction is the mental feeling of favourableness which an individual has about his job. It is often said that “A happy employee is a productive employee.” This shows that, job satisfaction is very important because most of the people spend a major portion of their life at their working place. Total of 76 respondents from UiTM Kampus Kota Bharu participate in this study by answering the questionnaires that I had given. From the result of questionnaire it shown that the all the factors have a positive relationship with job satisfaction. From the result it shows that all the independent variables are the biggest factors that lead to the job satisfaction among employee UiTM Kampus Kota Bharu. From the research I recommend a few suggestions for the future research on this topic. All about the factor that influence the job satisfaction will be discuss further in chapter 1 until 5 in the report.